Intervista a Michele Ranchetti - Ranchetti, Michele; Iannaco, Cecilia (Il sogno della farfalla, 2019)
This is the complete version (“Left” weekly published an abridged version earlier on) of an interview with Michele Ranchetti, editor of a new translation of Freud’s writings published by Bollati Boringhieri, which stirred up a controversy leading to the first two volumes being withdrawn from the market. Ranchetti gives us a rundown of the criteria underlying his work which aims to demonstrate that Freud’s language tends to be unscientific in nature and corrects certain terms which appeared in the previous translation edited by Musatti with Ranchetti’s collaboration because their meaning had been strained to render psychoanalysis more acceptable to the Italian culture. In addressing a number of questions and criticisms, Ranchetti analyzes terms like Besetzung, Wunsch, Verdrängung, Übertragung and Affekt highlighting Freud’s indiscriminate use of terms like Instinkt and Trieb, putting the controversy down to the scarce knowledge Italians have of the complex and rich nature of the German language.